Reinterpreting Flaubert and Lubis in Kardjo’s sonnets “L’Éducation Sentimentale”: A transcultural intertextuality study - Nurnaningrum, Sri; Umaya, Nazla Maharani; Harjito, Harjito (LITERA, 2025)
This article examines the transcultural intertextuality in Wing Kardjo’s sonnets “L’Éducation Sentimentale,” which reinterprets Gustave Flaubert’s novel with the same title and Mochtar Lubis’s novel Jalan Tak Ada Ujung. Using Julia Kristeva’s intertextuality framework,  the study examines how Kardjo adapts Lubis’s prose narrative into a sonnet form and reinterprets the thematic, narrative, and stylistic elements of Flaubert’s and Lubis’s novels. Through critical, comparative, and intertextual analyses, the research focuses on Kardjo’s innovative transformation of prose into structured poetic forms, preserving themes of love triangles, guilt, and political conflict. The results demonstrate how Kardjo repositions Lubis’s narrative within the structured form of sonnets and reframes Flaubert’s themes within Indonesia’s socio-political and cultural context. Through recontextualization and transformation, Kardjo creates a hybrid literary work that bridges French and Indonesian traditions, offering a transcultural dialogue that juxtaposes postcolonial struggles with existential disillusionment. This study concludes that Kardjo’s sonnets exemplify transcultural intertextuality as a creative process, enriching comparative literary studies and fostering cross-cultural dialogue through poetic innovation.